Could COVID-19 be a Catalyst for Disruption in Higher Education? (Comparative & International Education Series, 2021)
Advances in digital technologies have already transformed numerous industries, leading scholars to predict that online learning technologies would cause similar disruption in higher education. While these predictions have yet to be realized, will the COVID-19 pandemic change the situation?  This conceptual paper will draw from the authors’ complementary expertise in entrepreneurship, pedagogy, business and higher education organizational theory to address this question.  Using their disciplinary lenses and building on relevant literature in their field, each author will first identify key forces impacting change in higher education, and then discuss potential implications of faculty and students’ recent experience of remote teaching vis-a-vis those forces.  While highlighting the potential of the COVID-19 pandemic to accelerate disruption for higher education, the chapter will also suggest new ways in which universities may leverage the current experience to inform innovations that can actually strengthen their institution.